Parvulin 17-catalyzed tubulin polymerization is regulated by calmodulin in a calcium-dependent manner - Burgardt, Noelia Ines (2015)
Recently we have shown that the peptidyl-prolyl cis/trans isomerase parvulin 17 (Par17) interacts with tubulin in a GTPdependent manner, thereby promoting the formation of microtubules. Microtubule assembly is regulated by Ca2+-loaded calmodulin (Ca2+/CaM) both in the intact cell and under in vitro conditions via direct interaction with microtubule-associated proteins. Here we provide the first evidence that Ca2+/CaM interacts also with Par17 in a physiologically relevant way, thus preventing Par17-promoted microtubule assembly. In contrast, parvulin 14 (Par14), which lacks only the first 25 N-terminal residues of the Par17 sequence, does not interact with Ca2+/CaM, indicating that this interaction is exclusive for Par17. Pulldown experiments and chemical shift perturbation analysis with 15N-labeled Par17 furthermore confirmed that calmodulin (CaM) interacts in a Ca2+-dependent manner with the Par17 N terminus. The reverse experiment with 15N-labeled Ca2+/CaM demonstrated that the N-terminal Par17 segment binds to both CaM lobes simultaneously, indicating that Ca2+/CaM undergoes a conformational change to form a binding channel between its two lobes, apparently similar to the structure of the CaM-smMLCK796-815 complex. In vitro tubulin polymerization assays furthermore showed that Ca2+/CaM completely suppresses Par17-promoted microtubule assembly. The results imply that Ca2+/CaM binding to the N-terminal segment of Par17 causes steric hindrance of the Par17 active site, thus interfering with the Par17/tubulin interaction. This Ca2+/CaM-mediated control of Par17-assisted microtubule assembly may provide a mechanism that couples Ca2+ signaling with microtubule function.